Letter (copy) : Voluntary industrial aid - Citrine, Walter, 1887-1983
036-0030-001 WMC/WJB/AC/711 International 7th May, 1937. Mr. F.A. Smith, Amalgamated Engineering Union, 110, Peckham Road, S.E. 15. Dear Mr. Smith, VOLUNTARY INDUSTRIAL AID. With reference to our letter of 15th April last, we shall be glad to have from you a reply giving the views of your Executive on the full application of the proposals of the Voluntary Industrial Aid for Spain, as outlined therein. We have heard today from Mr. Geoffrey Pyke, the Hon. Secretary of the Voluntary Industrial Aid for Spain, that the Surgical Branch of your Union passed the following resolution:- "This Branch is prepared to support the Voluntary Industrial Aid for Spain if it can find a practicable way of doing the work." It is stated that "it" in the second line refers to the Voluntary Industrial Aid for Spain. Yours faithfully, General Secretary. 292/946/36/30